KETIMPANGAN PENDIDIKAN DAN PENDAPATAN DI INDONESIA - Adhitya Wardhana; Bayu Kharisma; Nurul S. J. (Bina Ekonomi, 2019)
AbstractThis study aims to determine the factors of educational and income inequality decreased in Indonesia. Several factors affect education inequality and income inequality such as government spending in education and urbanization. The data used are secondary data in the form of panels for the period 2010 to 2017 as many as 33 provinces in Indonesia. The research method used is 2SLS (two stage least squares) with fixed effects selected as the best parameter estimation method. The results of this study explain income inequality is influenced by education inequality variables and income inequality lag, which is significantly positive while per capita economic growth and urbanization variables do not have a significant effect on income inequality that occurs in Indonesia. While educational inequality is influenced by government spending in education and urbanization with a significant negative effect and lag of educational inequality has a significant positive effect on educational inequality. The income inequality has an insignificant effect on educational inequality.Keywords: income inequality; educational inequality; 2SLS